EFEKTIVITAS PENGGUNAAN LISENSI CREATIVE COMMONS SEBAGAI PERLINDUNGAN HAK CIPTA TERHADAP LAGU INDIE PADA PERUSAHAAN NETLABEL DI INDONESIA - , SEKAR AYU SATYANINGRUM, Prof. M. Hawin, S.H., LL.M., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to determine the effectiveness of the use creative commons license as copyright protection against indie tracks on netlabel companies in Indonesia, the legal relationship and the legal consequences indie song writer with netlabel companies over the use of creative commons license as a copyright protection. This research is a descriptive normative legal research, this research includes aspects of the application of the law by providing exposure, overview and analysis. Data obtained by research literature to obtain secondary data, and secondary data to complete fieldwork to obtain primary data by interviewing informants. The results showed that: the legal relationship between the indie song writer and netlabel company over use creative commons license as copyright protection treaty is an online distribution of copyrighted works where the netlabel company in carrying out its obligations to distribute copyrighted works owned by the creator or creators use creative commons license to protect copyrighted works are distributed, creative commons license itself does not conflict with the Copyright Act of the Republic of Indonesia. Legal consequences of the use of creative commons license as protection of creative works in this case is that creator of indie songs that use creative commons license as a protection upload their work will be protected from the creative commons such as in Indonesia, the creator who uses this license will get a defense of creative commons Indonesia if the creators of copyrighted works without citing sources hijacked, defense, among other creative commons Indonesia will be give piracy warning letter to the perpetrator, the perpetrator sends subpoena on piracy, bring the perpetrators and victims of piracy and provide support for legal defense mediation. Keywords: Creative Commons License, Copyright, Netlabel Companies, Indie Songs.